No farmer is an Island: Mechanisms behind successful climate services in and around Honduras - Giraldo Mendez, Diana (2023)
This thesis advances our understanding of what it means to establish participatory climate services for small- scale farmers on the ground in two main and contrasting agricultural systems—coffee and staple grains. Employing a mixed-methods approach that integrated participatory tools, farmer questionnaires, focus groups, in-depth interviews with farmers, and various actors in a case study, the research found that placing the farmer at the core the climate services development encouraged them to make their own decisions based on the analysis of information and their needs (98%, n = 209 famers in the Dry Corridor in Honduras), shifting away from the traditional top-down approach. This helped to establish an evaluation framework that supports the long-term sustainability of this service through a multi-stakeholder network involving at least 279 institutions across various levels and with diverse roles in four countries in Latin America. Collectively, the elements of this thesis contribute to a wider discourse on the factors influencing the success of climate services in terms of effectiveness, sustainability, and scalability, as well as a deeper comprehension of what determines "farmer participation" in climate services. The thesis also synthesizes an extensive body of systematic literature that has emerged within the climate service for agriculture domain over the past decade, augmenting our overall understanding of the nature of climate services, their evolution, and the existing gaps and challenges. The framework developed in this research is a valuable tool for advancing climate services research and informing the design and evaluation of interventions that cater to farmers' specific needs. Emphasizing participatory engagement and diverse representation has fostered a robust governance framework that strengthens rural development and resilience at the community level.